Optimalisasi Pengawasan Petugas Apron Movement Control Dalam Menjaga Kebersihan Apron Guna Menunjang Keselamatan Penerbangan Di Bandar Udara Internasional Mopah Merauke Papua - Dinda Melani; Suprapti (Universitas Sains dan Teknologi Komputer, 2023)
One of the airport service units is Apron Movement Control (AMC). AMC officers have the duties of being in charge of flight operations, monitoring aircraft movements, vehicle traffic, passengers and supervision of cleanliness in the airside area and recording flight data on the apron. Supervision is not only carried out on the movement of vehicles but also carried out on the cleanliness of the apron. The condition of the apron at Mopah Merauke International Airport still often occurs due to negligence by officers such as spills of aircraft fuel on the apron and scattered paper which can have an impact on safety and inconvenience for air transportation users. The purpose of this study was to find out how the AMC unit optimizes supervision of cleanliness on the apron and to find out the obstacles faced by the AMC unit in optimizing supervision of cleanliness on the apron to support flight safety at Mopah Merauke Airport, Papua. This research used qualitative research methods. This research was conducted on March 1 2023 – March 31 2023. The data collection techniques used were observation, interviews and documentation. Researchers directly make observations in the field as well as do documentation. The data analysis technique used is data reduction, data presentation, discussion and conclusion. The results showed that optimizing supervision of cleanliness on the apron of Mopah Merauke International Airport is very important to maintain flight safety, increase operational efficiency where AMC officers carry out cleanliness inspections on the apron of Mopah Merauke International Airport once per 1 week, starting from the apron area to the runway area and AMC officers who are on duty on the apron must always pay attention to the apron area every time before the aircraft heads to the taxiway (parking lot) so that there are no FODs. For AMC's obstacles in optimizing supervision of the cleanliness of the apron, namely extreme weather such as heavy rain, strong winds, or flooding and airline officials who are not compliant or do not care enough about trash and FOD.